Análise dos padrões de urbanização a partir da configuração espacial: o caso do município de Viana - Guimaraes, Andre Augusto Pereira (2022)
This dissertation seeks to understand the patterns of dispersed urbanization in the Municipality of Viana, between the years 1970 and 2020, through the analysis of spatial relationships, between parts, in a synchronous and diachronic way, its degree of accessibility and centrality with the use of the theoretical-methodological tools of space syntax (HILLIER; HANSON, 1984). Combining a qualitative and quantitative analysis, in addition to the configurational approach, with space syntax, it also used historical geographical and typological design approaches, in which it analyzed historical maps for the reconstruction of the urban fabric and analyzes of land uses and occupations. We worked with the hypothesis that the insertion, in the municipal limits, from the 1970s onwards, of the federal highways BR-101/ BR-262, altered the past spatial pattern, altering the patterns of connectivity, integration and accessibility in terms of spatial configuration, making the municipal fabric fragmented and dispersed. Thus, urbanization patterns dispersed throughout the territory were identified, naming them as connected, edge or disconnected. It was verified that the most integrated portion of the territory and with the best choice values are concentrated on the federal highways BR-101/ BR-262 or close to them, it was also verified that in this portion of the territory the connected urbanization patterns are also concentrated. and edge. It is therefore concluded that the space syntax, combined with its topological and geometric variables, and the identification of urbanization patterns, made it possible to confirm that the federal highways structured and structure the territory, is the road system responsible for linking the intra-urban and regional connections of the municipality and responsible for the fragmentation and dispersion of the territory.